Are Urban Heat Islands a threat to air transport? - Arkadiusz Bylica; Anton Pashkevich (Przegląd Komunikacyjny)
Abstract: Weather conditions always have a huge impact on air transport. Taking into account global climate changes, which have a great influence on such conditions, this problematic continues to be one of the most current research topics, especially in the context of the above-mentioned field of transport. This article attempts to present the issue of the Urban Heat Island (UHI) and its potential influence on air transport. The aspects of lightning discharges and torrential rains, which are often accompanying them, were also discussed. Additionally, infrastructural and procedural solutions reducing the negative effects of unfavourable weather conditions are described.